Potential of the Tourism Ecosystem of the Pahlawan Street Center Area of Madiun City from a Halal Tourism Perspective - Fadya Septia Putri; Luhur Prasetiyo (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
The development of halal tourism-based tourism is being intensively promoted. The potential in the Pahlawan Street Center area as a leading tourist destination in the Madiun City area and the availability of its halal ecosystem make the area an opportunity if the area is developed into a halal tourism area. From the potential of global trends and national goals regarding the development of halal tourism in Indonesia, this makes researchers interested in conducting this research. This study uses qualitative methods and a descriptive approach. This type of research uses field research. Data collection techniques from this study are from interviews, observations and documentation. The data analysis technique in this study used the inductive method, namely from general to specific discussions and with SOAR analysis. The results of this study explain that first the Pahlawan Street Center area has great potential to be directed into a halal tourism. Second, the opportunities in this area include the potential of the collaboration of various pentahelix parties who are actively involved in developing this tourist area. Third, the development strategy for this area is to utilize infrastructure and tourist attractions to build this area as a tourist destination whose ecosystem implements halal tourism.